From the first care to the postoperative period of the polytraumatized patient (Research, Society and Development, 2023)
Introduction: A patient is considered polytraumatized when he presents lesions in two or more systems of the human body. These injuries are serious and present a vital risk for the patient, requiring a multidisciplinary treatment and approach due to the complexity of the injuries usually resulting. Objective: To analyze the conducts carried out from the first consultation to the postoperative period of the polytraumatized patient. Methodology: This article falls under the integrative literature review category. For the composition of this work, the databases of scientific articles were used to carry out the searches: US National Library of Medicine (PubMed) and Scientific Electronic Library Online (SciELO) Latin American and Caribbean Literature in Health Sciences (LILACS) and Virtual Library in Health (VHL) where scientific data collection took place until January 11, 2023, in English, Portuguese and Spanish. The period analyzed for the selection of articles was from 2000 to 2022. The keywords “emergency” AND “polytramatized” AND “conducts” were used. Result and discussion: The conducts taken in polytraumatized patients involve procedures performed within the pre-hospital environment and the in-hospital. Thus, it is essential that the teams communicate at the time of patient management, with details and a detailed anamnesis. Conclusion: More studies and research on the subject are needed, mainly addressing the main behaviors that generate the most deaths in these patients.